2021
DOI: 10.3390/ani11041081
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Assessment of the Viability and Functionality of Uterine Polymorphonuclear Leukocytes in Postpartum Dairy Cows

Abstract: Postpartum dairy cows experience impaired peripheral polymorphonuclear leukocyte (PMN) functionality, which has been associated with reproductive tract inflammatory diseases. However, it has not been elucidated yet whether endometrial PMN functionality is (equally) impaired. We developed a method for endometrial PMN isolation and flow cytometric assessment of their viability and functionality. We also evaluated PMN immunolabeling, using a specific bovine granulocyte marker, CH138A. Blood and endometrial cytobr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Using previously established centrifugation protocols (Roth and Kaeberle 1981 ), we isolated Peripheral Blood Mononuclear Cells (PBMC), and PMNs. After staining our fractionated PBMC or PMN cell fractions using an anti- bovine granulocyte monoclonal antibody (GR-1) (Etchevers et al 2023 ; Lietaer et al 2021 ; Lopes et al 2021 ; Oliveira et al 2020 ), we found that our PMN fraction was viable, and had a PMN identity, as anti-GR-1 reactivity was very high in all of the PMN cells, but few of the PBMC cells (Fig. 1 A).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Using previously established centrifugation protocols (Roth and Kaeberle 1981 ), we isolated Peripheral Blood Mononuclear Cells (PBMC), and PMNs. After staining our fractionated PBMC or PMN cell fractions using an anti- bovine granulocyte monoclonal antibody (GR-1) (Etchevers et al 2023 ; Lietaer et al 2021 ; Lopes et al 2021 ; Oliveira et al 2020 ), we found that our PMN fraction was viable, and had a PMN identity, as anti-GR-1 reactivity was very high in all of the PMN cells, but few of the PBMC cells (Fig. 1 A).…”
Section: Resultsmentioning
confidence: 86%
“…Isolated leukocytes were stained with anti- bovine GR-1 antibody to confirm PMN identity, as previously described (Etchevers et al 2023 ; Lietaer et al 2021 ; Lopes et al 2021 ; Oliveira et al 2020 ). Briefly, cells were stained with mouse anti-bovine granulocyte (GR-1) monoclonal IgM primary antibody (clone-CH138A, Kingfisher Biotech), or isotype control (clone-COLIS52A2, Kingfisher Biotech) at a concentration of 1.0 ug/mL, followed by a FITC goat anti-mouse IgM polyclonal secondary antibody (ThermoFisher) at a concentration of 1.5 ug/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Our research group has recently developed a technique to flow cytometrically to evaluate the viability and functionality of uterine neutrophils collected via the cytobrush technique (Lietaer et al, 2021, 2022). In new, unpublished data collected from 32 dairy cows at 9, 21, and 36 postpartum, we found that uterine neutrophils in the fifth week postpartum are mostly necrotic in healthy cows, but viable and functional in cows with clinical endometritis.…”
Section: Effects Of Transition Period Maladaptation On Reproductive O...mentioning
confidence: 99%